Comparative study to some semi numerical methods for solving nonlinear Wave-like Equations with variable coefficient - Riyadh, Mohanad (University of Thi-Qar Journal of Science, 2019)
In this paper we solve the nonlinear wave-like Equations with variable coefficient by three Semi numerical methods, varational iteration method (VIM), homotopy perturbation method (HPM) and homotopy analysis method (HAM). The solution obtained by these methods are Compared with the solution obtained by Adomian decomposition method (ADM) and the exact solution [8].